Long-term monitoring reveals the success of salmonid habitat restoration - Louhi, Pauliina; Vehanen, Teppo; Huusko, Ari; Mäki-Petäys, Aki; Muotka, Timo (NRC Research Press (a division of Canadian Science Publishing), 2016)
The growing concern on declining salmonid populations has resulted in numerous restoration projects with variable responses worldwide. In this spatially replicated multi-year study, we assessed the long-term (12 years post-restoration) effects of in-stream habitat restoration (i.e. addition of boulders or large woody debris (LWD) together with boulders) on densities of three age-classes of juvenile brown trout in six forest streams in northern Finland. LWD combined with boulders was more beneficial, particularly for the larger trout (age-2 and older), than were boulder structures alone, indicating that the more diverse habitat created by LWD may have provided a safeguard against drought for the larger fish. Density of age-0+ trout showed a significant long-term increase in boulder-restored sections, providing evidence that log structures may need to be complemented by stony enhancement structures to guarantee the availability of suitable stream habitat for all trout age-classes. As trout densities are known to exhibit inherently wide inter-annual variability that tracks climatically-induced hydrological variation, long-term post-restoration monitoring that encompasses extreme hydrological events is critical for evaluating the success of restoration projects. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.